Pengaruh Budaya Organisasi dan Perilaku Manajerial terhadap Efektivitas Penganggaran dan Keberlanjutan Keuangan Perusahaan - Novia Ardana Siregar; Misjelina Br Surbakti; Anggun Nabila; Yusril Anwar; Muammar Khaddafi (Jurnal Publikasi Ilmu Manajemen, 2025)
Organizational culture and the way managers think and act significantly influence the quality of the budgeting process and the overall financial stability of a company. A work environment characterized by strong shared values, clear rules, ethical standards, and effective communication can enhance collaboration among employees and contribute to more accurate, transparent, and realistic budgeting practices. Conversely, managers’ behavior reflected through consistency, integrity, accountability, leadership commitment, and sound decision-making skills also plays a crucial role in determining the accuracy of budget implementation, monitoring, and expenditure control. When organizational culture and managerial behavior are aligned and mutually reinforcing, the budgeting process becomes more efficient, disciplined, and adaptive to organizational needs. This alignment supports better allocation of financial resources and reduces the risk of budget deviations. As a result, organizations are better positioned to maintain financial control and achieve long-term financial sustainability. Therefore, the integration of a strong organizational culture with positive managerial behavior serves as an essential foundation for establishing a sound, flexible, and sustainable financial management system that supports organizational performance and strategic objectives.